Enforcing International Law : From Self-help to Self-contained Regimes. - Noortmann, Math (Ashgate Pub., 2007)
This study determines which rules and principles govern the relationship between the two basic concepts of the right to self-help and the obligation to settle disputes by peaceful means. Drawing insights from legal as well as political science, the book's.